Analisis Faktor-Faktor yang Berpengaruh terhadap Persediaan Pada Usaha Kain Sasirangan Di Kota Banjarmasin - Abd Wahab HJ (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This research is aimed to analize factors that affect the inventory of Sasirangan business in Banjarmasin. The factors analized in the research are: selling amount (X1), product amount (X2), price level (X3), product variety (X4), material purchase amount (X5), lead time (X6), and inventory amount (Y). For about 25 samples that meet the requirements will be taken by using the purposive sampling technique. The analysis tool that is used in this research is the multiple linear regression model; regression equations, that show the variables X1, X2, X3, X4, X5, X6, simultaneously give significant effect to variable Y. This is shown in the test F result that the F calculation (11.244) is higher than the table F (2,66), and its probability value (2.947E-05) is lower than the value of alfa (? = 0,05). While the dominant factor that affects inventory amount of Sasirangan business in Banjarmasin is the selling amount (X1).Key words: selling amount, product amount, price level, product variety, material purchase amount, lead time, and inventory amount..